CFD analysis of splitter plate on bluff body - Aabid, Abdul; Afifi, Azmil; Mehaboobali, Fharukh Ahmed Ghasi; Akhtar, Mohammad Nishat; Khan, Sher Afghan (Penerbit Akademia Baru, 2019)
The blunt base either in the front or at the rear portion of the vehicles is prevalent and is found in railways where the front and rear portions the coaches are blunt, which results in zero velocity and hence the stagnation pressure, which is undesirable. The aim of this study is to investigate the effect of the splitter plate on the wake control of a bluff body. A rectangular bluff body of dimension 50 mm x 60 mm is controlled by a splitter plate positioned at the front of the bluff body as a passive control technique. The variation of the splitter plate length with respect to the height of the bluff body was considered. In the present study, K-epsilon enhanced wall treatment turbulence model has been used for the validation of the simulation results with the existing experimental data. The experimental results agree with the simulation's results with a significant impact of upstream splitter plate on the drag reduction in a turbulent flow. From the results, it is found that the splitter plate is useful to decrease the drag by controlling the flow field.